If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -4) = -16 Reorder the terms: 4(-4 + 3x) = -16 (-4 * 4 + 3x * 4) = -16 (-16 + 12x) = -16 Add '16' to each side of the equation. -16 + 16 + 12x = -16 + 16 Combine like terms: -16 + 16 = 0 0 + 12x = -16 + 16 12x = -16 + 16 Combine like terms: -16 + 16 = 0 12x = 0 Solving 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '12'. x = 0 Simplifying x = 0
| 15+0.05x=57 | | z^2=85 | | 11 = y/3+ 8 | | 6p^2=31p-5 | | 15+50m=25+25m | | ax+box=c | | -4=2x+10 | | 43-(x+9)=8x-2 | | 6(5x+7)+4x-10=7 | | 10c+100-5c=-225 | | 4-0.4(3d)=12 | | x+4a=17+ax-6a | | 17/y+y/y+32/y+y/y=100 | | 2/5p=-4/7 | | -2(-3x-2)=-14 | | 2r^2-16r-40=0 | | 4/5x+4=8 | | 8-y^3=0 | | h/-3+ 9= 12 | | X+20=-5y | | 6(5x+7)4x-10=7 | | 3(2t-0.71)=0.9(1.4-t) | | 2-3/8x=7 | | x+33=98 | | 0.12y+0.06(y+2000)=1020 | | 6x+5=-9x+6 | | -3y-15= | | 26=8-m | | 48=15+.05x | | .16x+.6(x-4)=.01(2x-1) | | 15-w/4=23 | | 112=7xb |